Blood eosinophil count and exacerbation risk in patients with COPD. Issue 1 (20th July 2017) - Kerkhof, Marjan; Sonnappa, Samatha; Postma, Dirkje S.; Brusselle, Guy; Agustí, Alvar; Anzueto, Antonio; Jones, Rupert; Papi, Alberto; Pavord, Ian; Pizzichini, Emilio; Popov, Todor; Roche, Nicolas; et al.
Exacerbations in chronic obstructive pulmonary disease (COPD) are major contributors to worsening lung function, impaired quality of life, emergency healthcare use and COPD-related mortality. COPD exacerbations are heterogeneous in terms of airway inflammation and aetiology. About 60% of COPD patients have blood eosinophil counts of ≥2%, which appears to be associated with an increased risk of exacerbations [1–3]. However, the association between blood eosinophil counts at stable disease and COPD exacerbations in the subsequent year is incompletely understood. Blood eosinophil count may serve as a biomarker of exacerbation risk in subgroups of patients with COPD http://ow.ly/6tm530cEAeO